2016
DOI: 10.1002/jor.23305
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion to suture material in a contaminated wound model: Comparison of monofilament, braided, and barbed sutures

Abstract: Contaminated suture material plays an important role in the physiopathology of surgical site infections. Recently, suture material has been developed characterized by barbs projecting from a monofilament base. Claimed advantages for barbed sutures are a shortened wound closure time and reduced maximum wound tension. It has also been suggested that these sutures would be advantageous microbiologically. The aim of this study was to test the microbiological characteristics of the barbed Quill in comparison to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 53 publications
1
31
0
2
Order By: Relevance
“…While this characteristic lends itself to an improved suture-tissue interface and pull-through resistance, the broadened shape and subsequent increased surface area of FiberTape may also portend increased surgical complications, such as infection. Previous studies have demonstrated the increased bacterial adherence of braided versus monofilament sutures, 6,14 and we have shown that this also applies to increased surface area of otherwise similarly composed high–tensile strength sutures. In addition to an increased risk of acquiring an infection in the presence of bacteria (group 1), our findings suggest that FiberTape has an increased risk of retaining infection even after simulated washout procedures (groups 2 and 3).…”
Section: Discussionsupporting
confidence: 67%
“…While this characteristic lends itself to an improved suture-tissue interface and pull-through resistance, the broadened shape and subsequent increased surface area of FiberTape may also portend increased surgical complications, such as infection. Previous studies have demonstrated the increased bacterial adherence of braided versus monofilament sutures, 6,14 and we have shown that this also applies to increased surface area of otherwise similarly composed high–tensile strength sutures. In addition to an increased risk of acquiring an infection in the presence of bacteria (group 1), our findings suggest that FiberTape has an increased risk of retaining infection even after simulated washout procedures (groups 2 and 3).…”
Section: Discussionsupporting
confidence: 67%
“…The role of suture material as a contributing factor to SSIs has been the subject of research since the 1970s [69]. The suture structural parameters are a crucial parameter that influences the adhesion of bacteria, and roughness on a nanoscale has been shown to be beneficial for pathogen adhesion to biomedical material [70]. The morphology of silk surgical threads can promote bacterial accumulation between the grooves of its multifilament thread, enhancing the risk of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting aspect is that TIAB explicates its antibacterial and antibiofilm activity even when complexed with other components in the form of cream, providing that this combination does not inhibit its efficacy. In addition, no differences in the biofilm formation were registered on the three different braided multifilament sutures, thus confirming the broad MD versatility after surgery, as demonstrated for triclosan-coated sutures [27].…”
Section: Resultsmentioning
confidence: 57%